Evolutionary Game Research between the Government Environmental Regulation Intensities and the Pollution Emissions of Papermaking Enterprises - Sen Zhang; Guangyuan Qin; Ling Wang; Baodong Cheng; Yuan Tian (Discrete Dynamics in Nature and Society)
Environmental regulations of different intensities may have different impacts on polluting enterprises. The purpose of this article is to analyze how different environmental regulations affect the pollution discharge strategies of papermaking enterprises. By establishing an evolutionary game model between the government environmental regulation intensities and the pollutant emissions from papermaking enterprises, this thesis further solves the model and performs stability analysis and finally uses MATLAB to conduct simulation studies. And the researching results show that papermaking enterprises will take risks to choose the illegal pollutant discharge strategies when the illegal profits are large. Further analysis shows that the increase in the successful probability of the strong environmental regulations does not necessarily force papermaking enterprises to choose to comply with pollution discharge regulations. However, papermaking enterprises may choose to comply with discharge pollution regulations not only by increasing the successful probability of strong environmental regulations but also by increasing the rewards and punishments for papermaking enterprises as well as by increasing the probability of reporting violations of pollutants. Based on the above results, the author proposes several countermeasures, such as establishing a specialized pollution monitoring agency, encouraging third-party supervision, reporting pollution behaviors, and increasing penalties for polluting companies for violations. China is in a critical period of transition from rapid development to high-quality development. It will provide some reliable references for the construction of a green economy and an ecological economy that the characteristics and relationships between the intensity of government environmental regulations and corporate pollution emissions revealed in this article.